Who gets included? A scoping review protocol of digital health interventions for older adults with heart failure through an equity lens - Kristina M. Kokorelias; Peter Hoang; Maurita T. Harris (PLoS ONE, 2025)
Introduction Heart failure is a common and progressive condition that significantly impacts older adults, leading to increased morbidity, reduced quality of life, and healthcare utilization. As its prevalence continues to rise, there is a need for effective management strategies tailored to this population. Digital health interventions (DHIs) have emerged as promising tools for managing chronic conditions like heart failure, potentially improving accessibility and personalizing care. However, there is limited understanding of the inclusivity and effectiveness of these interventions across diverse subgroups of older adults, particularly those differentiated by age, cognitive status, socioeconomic status, sex/gender, and race/ethnicity. Methods This protocol outlines a scoping review to assess the extent of literature on DHIs for managing heart failure among older adults, focusing on the representation of diverse subgroups and the characteristics of the interventions. Specifically, the review will explore which populations are included in current DHIs, how they are represented, and how intervention characteristics influence participation and outcomes. This scoping review will follow the Joanna Briggs Institute methodology for scoping reviews, using the PROGRESS-Plus framework to assess equity-related factors such as socioeconomic status, race/ethnicity, geographic location, and cognitive status. The review will focus on randomized controlled trials published between January 1, 2005, and the present, in high-income countries. Conclusions The forthcoming scoping review will provide a comprehensive mapping of the existing literature on digital health interventions for heart failure management in older adults, focusing on the inclusivity of diverse subgroups. By identifying gaps in the representation of key demographic factors such as age, cognitive status, socioeconomic status, sex/gender, and race/ethnicity, the review will highlight areas for future research and inform the development of more equitable, effective digital health solutions for heart failure. The findings will be valuable for healthcare practitioners, policymakers, and researchers seeking to improve the accessibility and impact of DHIs in managing heart failure among older populations.